2021
DOI: 10.1007/s00204-021-03015-1
|View full text |Cite
|
Sign up to set email alerts
|

Physiologically based kinetic modelling based prediction of in vivo rat and human acetylcholinesterase (AChE) inhibition upon exposure to diazinon

Abstract: The present study predicts in vivo human and rat red blood cell (RBC) acetylcholinesterase (AChE) inhibition upon diazinon (DZN) exposure using physiological based kinetic (PBK) modelling-facilitated reverse dosimetry. Due to the fact that both DZN and its oxon metabolite diazoxon (DZO) can inhibit AChE, a toxic equivalency factor (TEF) was included in the PBK model to combine the effect of DZN and DZO when predicting in vivo AChE inhibition. The PBK models were defined based on kinetic constants derived from … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
22
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(23 citation statements)
references
References 77 publications
(127 reference statements)
1
22
0
Order By: Relevance
“…Performing the QIVIVE of the in vitro AR-CALUX derived concentration-response curve to generate a dose-response curve for the anti-androgenic effect of FLU taking the activity of HF into account, a toxic equivalency factor (TEF) approach ( Zhao et al, 2021 ) was included in the PBK model to predict the combined free C max values of FLU and HF expressed in FLU equivalents ( Eq. 6 ).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Performing the QIVIVE of the in vitro AR-CALUX derived concentration-response curve to generate a dose-response curve for the anti-androgenic effect of FLU taking the activity of HF into account, a toxic equivalency factor (TEF) approach ( Zhao et al, 2021 ) was included in the PBK model to predict the combined free C max values of FLU and HF expressed in FLU equivalents ( Eq. 6 ).…”
Section: Methodsmentioning
confidence: 99%
“…To use this TEF approach, 3 criteria need to be met ( Zhao et al, 2021 ). First, FLU and HF act via the same mode of action.…”
Section: Methodsmentioning
confidence: 99%
“…Furthermore, chapter 4 assessed the combination effects of PPF and CPO, the toxic metabolite of CPF, on human recombinant AChE activity in vitro also translating these effects upon combined exposure to the in vivo situation, while Chapter 5 predicted human interindividual differences in PPF detoxification based on a combined in vitro-in silico approach. These studies add to previous work that reported the suitability of PBK models to predict OP dose-dependent in vivo AChE inhibition using PBK modeling-facilitated reverse dosimetry of in vitro data, for example for malathion CPF and diazinon (Zhao et al, 2021). In order to allow risk assessors to implement this alternative testing strategy, more proofs-of-principle using this approach with more OPs would be of use and provide a topic for future work in which the approach may prove to be of general use for OP risk assessment.…”
Section: Use Of Alternative Testing Strategies and How They Can Be Us...supporting
confidence: 53%
“…For chemicals that follow the concept of concentration addition in vitro, the RPF approach as used in the current study for CPO and PFF in the PBK model could be extended in the future to also include other OPs and carbamates, allowing a more extensive assessment of the combined exposure to OPs and carbamates based on novel approach methods (NAMs) as applied in the present study. Such an approach to include data for more than one chemical has recently been used by our group to predict in vivo human and rat RBC (AChE) inhibition upon acute exposure to diazinon and its active metabolite, diazinon oxon (Zhao et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…In the present study, the inhibitory effect of the active CPF metabolite CPO on RBC AChE was measured using rhAChE, as a proxy for RBC AChE, using the method previously published (Zhao et al 2021 ), based on the method from Ellman et al ( 1961 ). The working solutions were prepared by diluting a series of increasing concentrations of CPO (in ethanol) 50-fold in 100 mM sodium phosphate (pH 7.4) containing 0.1 mg/ml BSA.…”
Section: Methodsmentioning
confidence: 99%